Parametric study of the radial plasma-wall interaction in a Hall thruster. (9th September 2019) - Domínguez-Vázquez, A; Taccogna, F; Fajardo, P; Ahedo, E
Abstract: An investigation on the influence of relevant parameters on an annular Hall effect thruster plasma discharge is performed using a radial particle-in-cell simulation code with secondary electron emission from the walls and prescribed axial electric and radial magnetic fields. A simulation with true-secondary electrons only is taken as reference. First, the near-wall conductivity effects on the magnetized secondary electrons are illustrated by doubling the, allowing a further code validation. Second, when secondary backscattered electrons are included, the enhanced secondary emission yields lower sheath potential drops and primary electron temperature. Moreover, the dominant backscattered electrons increase the average secondary electrons emission energy, greatly affecting its temperature anisotropy ratio and increasing the replenishment level of the wall collectable tails of the primary electrons velocity distribution function. Third, the effect of the true-secondary electrons emission energy on the potential profile is shown to be negligible, the latter being mainly set by the dominant magnetic mirror effect. Finally, a planar case featuring symmetric plasma profiles permits to confirm the validity of the large cylindrical asymmetries present in the reference case, induced by the combined effects of the geometric expansion, the magnetic mirror and the centrifugal force (due to the drift). A smaller deviation of the primary electron momentum equation from the Boltzmann relation along the magnetic lines is still found in the planar case, induced by the parallel temperature non-uniformity.